Analisis Kemauan Politik Pemerintah dalam Mewujudkan Kedaulatan Data melalui Kebijakan Pengembangan Pusat Data Nasional - Aji, Muhammad Prakoso; Yuliandri, Putrawan (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
Data sovereignty has become an increasingly strategic issue in the digital era, as data now constitutes a critical asset shaping national security, economic competitiveness, and governance capacity. In response to growing concerns over fragmented data governance and recurring data breaches, the Indonesian government initiated the development of the National Data Center (Pusat Data Nasional/PDN) as a key infrastructure for strengthening national data sovereignty. This study examines the extent to which political will supports the realization of data sovereignty through the PDN development policy. Using a qualitative descriptive approach, this research analyzes policy documents, regulatory frameworks, and secondary data related to Indonesia’s data governance initiatives. The analytical framework is based on Brinkerhoff’s concept of political will, which identifies seven key components: government initiative, policy selection, stakeholder mobilization, public commitment and resource allocation, credible sanctions, sustainability of efforts, and learning and adaptation. The findings reveal that Indonesia’s political commitment toward data sovereignty remains partial and uneven. While several components of political will, such as government initiative, policy formulation, stakeholder mobilization, resource allocation, and continuity of policy efforts, have begun to emerge, other crucial elements, particularly credible sanctions and institutional learning mechanisms, remain underdeveloped. The absence of comprehensive implementing regulations under the Personal Data Protection Law and the delayed establishment of an independent data protection authority further weaken the institutional foundation for national data sovereignty. This study argues that strengthening political will is essential to accelerate the implementation of the National Data Center and to build an integrated national data governance system. Without stronger regulatory commitment and institutional coordination, Indonesia risks lagging behind other countries in securing digital sovereignty and protecting strategic national data in the evolving global digital economy.